2023
DOI: 10.32479/ijeep.14189
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Highest Prices and Trading Volume in the Share Indices of Energy and Oil Companies in Kazakhstan

Abstract: This study uses econometric methods to reveal the relationship between the highest price formation and trading volume in the share indices of energy and oil companies traded on the Kazakhstan Stock Exchange (KASE). The study used daily transaction data of KEGC, KZAP, and KZTO companies for 200 trading days in 2022. The analysis is based on the VAR method. The shock effect analysis concluded that there is a mutual interaction between the trading volume and the highest price formation for all three companies. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This finding indicates a substantial decline in the amount of investor demand for Sharia stocks throughout that period. The conclusions of this study align with the research undertaken by Zhussipova (2023), which also demonstrates that the capital market is not responsive to news about gasoline price hikes. The findings of this study are consistent with the research undertaken by Ardani (2019), which concluded that there was no discernible disparity in anomalous returns before and after the announcement of the gasoline price hike on January 5, 2017.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding indicates a substantial decline in the amount of investor demand for Sharia stocks throughout that period. The conclusions of this study align with the research undertaken by Zhussipova (2023), which also demonstrates that the capital market is not responsive to news about gasoline price hikes. The findings of this study are consistent with the research undertaken by Ardani (2019), which concluded that there was no discernible disparity in anomalous returns before and after the announcement of the gasoline price hike on January 5, 2017.…”
Section: Discussionsupporting
confidence: 84%
“…An African stock portfolio provides protection against the volatility of global crude oil price changes.The study findings indicate notable disparities in trading volume as a consequence of the announcement of the hike in fuel prices. In their study,Zhussipova et al (2023) examined the significance of the relationship between trading volume and price formation in the context of investment decisionmaking. Some investors are willing to embrace unpredictable conditions.…”
mentioning
confidence: 99%